Heat-conducting gel as well as preparation method and application thereof
By developing a thermal conductivity gel with a thermal conductivity coefficient of 10W/m·k~15W/m·k, the problem that existing TIMs cannot meet the chip heat dissipation needs is solved, and efficient chip heat dissipation performance is achieved, and overheating damage is avoided.
Patent Information
- Application Number
- CN202411994438.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Existing thermal interface materials (TIMs) cannot meet the chip's heat dissipation needs, resulting in overheating damage that may occur during long-term operation of the chip.
A thermal conductivity gel was developed with a thermal conductivity coefficient of 10W/m·k~15W/m·k and a bonding thickness of 15μm~25μm. Its thixotropy, viscosity and other properties were adjusted by adjusting the backup conditions.
High thermal conductivity and thin bonding thickness are achieved, the heat dissipation performance of the chip is improved, and overheating damage occurs due to untimely heat dissipation.
Smart Images

Figure BDA0005224293400000061 
Figure BDA0005224293400000081 
Figure BDA0005224293400000121
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of thermal interface materials, and specifically relates to a thermally conductive gel and a preparation method and application thereof. Background Art
[0002] In high-end processor chips, high-power LEDs, and other high-performance AI chip applications, FCBGA packaging technology, as the mainstream, places extremely high demands on heat dissipation performance. Chip heat dissipation requires reducing energy consumption while ensuring the stability and life of components. Thermal interface materials (TIM), also known as thermal conductive materials, thermal conductive interface materials, or interface thermal conductive materials, are a type of material commonly used in IC packaging and electronic heat dissipation. They are mainly used to fill the micro-gaps and uneven holes generated when two materials are joined or contacted, reduce the impedance of heat transfer, and improve heat dissipation. When the chip is packaged, most of the heat is dissipated from the top of the chip to the heat sink through the package. A high thermal conductivity thermal interface material is often required between the chip and the package to help transfer heat, so that the heat is transferred to the heat sink through multiple conduction of silicon wafer-internal thermal conductive material-CPU metal cover-external thermal conductive material. The most important feature of high-performance thermal interface materials is that they can transfer heat very quickly, so TIM is required to have low contact thermal resistance, high thermal conductivity, and low bonding thickness (Bond Line Thickness, BLT).
[0003] However, the contact thermal resistance (or thermal conductivity), thermal conductivity and bonding thickness of existing TIMs cannot meet the heat dissipation requirements of chips. If the chip is operated for a long time, it will be damaged by overheating due to untimely heat dissipation. Summary of the invention
[0004] To solve the above problems, the present application provides a thermally conductive gel and a preparation method thereof. The thermal conductivity of the thermally conductive gel is 10W / m·k to 15W / m·k. The preparation method adjusts the thixotropy, viscosity and other properties of the thermally conductive gel by adjusting the preparation conditions.
[0005] This application is implemented through the following technical solutions:
[0006] In a first aspect, the present application provides a thermally conductive gel, comprising the following raw material components in parts by weight:
[0007] 3 to 5 parts of vinyl silicone oil, 0.4 to 0.9 parts of hydrogen-containing silicone oil, 0.1 to 0.3 parts of coupling agent, 0.1 to 0.3 parts of tackifier, 0.002 to 0.02 parts of inhibitor, 0.02 to 0.04 parts of catalyst, and 90 to 98 parts of filler.
[0008] The thermally conductive gel provided in the present application has a thermal conductivity of 10W / m·k to 15W / m·k and a bonding thickness of 15μm to 25μm, and has the advantages of high thermal conductivity (low contact thermal resistance) and thin bonding thickness.
[0009] In some possible implementations, the vinyl content of the vinyl silicone oil is 0.4% to 0.5%.
[0010] In some possible implementations, the viscosity of the vinyl silicone oil is 400 cps to 500 cps.
[0011] In some possible implementations, the hydrogen-containing silicone oil includes 0.2 to 0.4 parts of terminal hydrogen silicone oil and 0.3 to 0.5 parts of pendant hydrogen silicone oil.
[0012] In some possible implementations, the hydrogen content of the hydrogen-terminated silicone oil is 0.1% to 0.14%, and the viscosity is 20 cps to 25 cps.
[0013] In some possible implementations, the hydrogen content of the side hydrogen silicone oil is 0.08% to 0.12%, and the viscosity is 60 cps to 80 cps.
[0014] In some possible implementations, the filler includes at least one of modified silver powder, modified diamond powder and zinc oxide.
[0015] In some possible implementations, the filler includes the following components in parts by weight:
[0016] 80 to 105 parts of modified silver powder, 10 to 20 parts of modified diamond powder and 3 to 7 parts of zinc oxide;
[0017] The modified silver powder is obtained by modifying silver powder;
[0018] The silver powder comprises 15 to 30 parts by weight of a first silver powder and 65 to 75 parts by weight of a second silver powder;
[0019] The average particle size of the first silver powder is 250nm to 350nm;
[0020] The average particle size of the second silver powder is 450nm-550nm.
[0021] In a second aspect, the present application provides a method for preparing the thermally conductive gel provided in the present application, comprising the following steps:
[0022] The raw materials of the thermal conductive gel are mixed to obtain the thermal conductive gel.
[0023] The method for preparing the thermally conductive gel provided in the present application can prepare the thermally conductive gel having a very high thermal conductivity and a very thin bonding thickness.
[0024] In some possible implementations, the mixing process includes the following steps:
[0025] After the vinyl silicone oil, hydrogen-containing silicone oil, coupling agent, tackifier, inhibitor and filler are subjected to a first mixing treatment, a second mixing treatment is performed with the catalyst.
[0026] In some possible implementations, the preparation of the filler comprises the following steps:
[0027] After the modified silver powder, modified diamond powder and zinc oxide are mixed, they are stirred at a rotation speed of 50 rpm to 100 rpm for 30 min to 40 min.
[0028] In some possible implementations, the preparation of the modified silver powder comprises the following steps:
[0029] Dispersing silver powder into a silver treatment agent and drying to obtain the modified silver powder;
[0030] The dosage of the silver treatment agent is 1% to 3% of the mass of the silver powder.
[0031] In some possible implementations, the preparation of the modified diamond powder comprises the following steps:
[0032] dispersing diamond powder into a diamond treating agent and drying to obtain the modified diamond powder;
[0033] The dosage of the diamond treatment agent is 0.5% to 2% of the mass of the diamond powder.
[0034] In some possible implementations, the first mixing process includes the following steps:
[0035] Vinyl silicone oil, hydrogenated silicone oil, coupling agent, tackifier and inhibitor are mixed, and then ultrasonically mixed at 55° C. to 65° C. for 15 to 25 minutes to obtain a first mixture;
[0036] After the first mixed liquid and the filler are mixed, they are stirred at a rotation speed of 50 rpm to 100 rpm for 25 min to 35 min, and then stirred at a temperature of 85° C. to 95° C. and a rotation speed of 200 rpm to 250 rpm for 1.5 h to 2.5 h to obtain a second mixed material.
[0037] In some possible implementations, the second mixing process includes the following steps:
[0038] After the second mixed material and the catalyst are mixed, they are stirred for 0.5 h to 1 h under vacuum at a rotation speed of 200 rpm to 250 rpm to obtain the thermal conductive gel.
[0039] In a third aspect, the present application provides an application of the thermally conductive gel provided in the present application in the field of chip heat dissipation. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0041] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.
[0042] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.
[0043] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution, and all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0044]
Thermal conductive gel
[0045] In a first aspect, an embodiment of the present application provides a thermally conductive gel, comprising the following raw material components in parts by weight:
[0046] 3 to 5 parts of vinyl silicone oil, 0.4 to 0.9 parts of hydrogen-containing silicone oil, 0.1 to 0.3 parts of coupling agent, 0.1 to 0.3 parts of tackifier, 0.002 to 0.02 parts of inhibitor, 0.02 to 0.04 parts of catalyst, and 90 to 98 parts of filler.
[0047] The thermally conductive gel provided in the embodiment of the present application has the advantages of high thermal conductivity, low viscosity, and thixotropy.
[0048] In some embodiments, the vinyl content of the vinyl silicone oil is 0.4% to 0.5%. In this case, a proper cross-linked network structure can be ensured to ensure its excellent mechanical properties.
[0049] In some embodiments, the viscosity of the vinyl silicone oil is 400 cps to 500 cps. In this case, the uniformity of the molecular weight of the vinyl silicone oil can be controlled to ensure the consistency of the activity of the vinyl silicone oil and the stability of the product.
[0050] In some embodiments, the hydrogen-containing silicone oil includes 0.2 to 0.4 parts of terminal hydrogen silicone oil and 0.3 to 0.5 parts of side hydrogen silicone oil. In this case, the terminal hydrogen silicone oil can improve the elasticity of the product, and the side hydrogen silicone oil can improve the modulus of the product. The two cooperate with each other to adjust the various mechanical properties of the product.
[0051] In some embodiments, the hydrogen content of the hydrogen-terminated silicone oil is 0.1% to 0.14% and the viscosity is 20 cps to 25 cps. In this case, the molecular weight uniformity of the hydrogen-terminated silicone oil can be controlled to ensure the consistency of the activity of the vinyl silicone oil and the stability of the product.
[0052] In some embodiments, the hydrogen content of the pendant hydrogen silicone oil is 0.08% to 0.12% and the viscosity is 60 cps to 80 cps. In this case, the molecular weight uniformity of the pendant hydrogen silicone oil can be controlled to ensure the consistency of the activity of the vinyl silicone oil and the stability of the product.
[0053] In some embodiments, the coupling agent includes at least one of dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, and hexadecyltriethoxysilane. In this case, these coupling agents have high boiling points, are not easily volatile, and have average siloxane activity, which can ensure that the product can be smoothly grafted with the powder under heating conditions to achieve the effect of reducing viscosity and increasing viscosity.
[0054] In some embodiments, the tackifier contains an active group, and the active group includes at least one of an epoxy group, an isocyanate group, and a vinyl group. In this case, curing poisoning will not occur, and the active group is easy to generate physical or chemical forces with the surface of the contact substrate, thereby improving the bonding performance of the product.
[0055] In the embodiment, the tackifier can be selected from the following materials:
[0056] RH-GZ-03 (containing vinyl) Zhejiang Runhe Silicone New Materials Co., Ltd.;
[0057] UM-DB2152 (containing benzene ring and epoxy group) Wuhan Enric Materials Co., Ltd.;
[0058] UM-T907 (containing vinyl and epoxy groups) Wuhan Enric Materials Co., Ltd.;
[0059] UM-T9152 (containing allyl / NCO / epoxy) Wuhan Enric Materials Co., Ltd.
[0060] In some specific embodiments, when the tackifier comprises a vinyl reactive group, the vinyl content is 1% to 4%.
[0061] In some embodiments, the inhibitor includes acetylene cyclohexanol. In this case, acetylene cyclohexanol as an inhibitor can balance the operable time and storage period of the product.
[0062] In some embodiments, the catalyst comprises a mixture of chloroplatinic acid and silicone oil, wherein the mass fraction of chloroplatinic acid is 0.5% to 1%. In this case, an appropriate catalyst concentration can avoid excessive local reaction activity and the resulting implosion.
[0063] In some embodiments, the filler includes at least one of modified silver powder, modified diamond powder, and zinc oxide.
[0064] In some embodiments, the filler includes the following components in parts by weight:
[0065] 80 to 105 parts of modified silver powder, 10 to 20 parts of modified diamond powder and 3 to 7 parts of zinc oxide.
[0066] In some embodiments, the zinc oxide is in the shape of a column or a rod, and the average particle size is 1 μm to 4 μm. In this case, the zinc oxide adjusts the thixotropy of the product, which is beneficial for dispensing; and the column or rod shape serves as a skeleton in the product to enhance the body strength of the product.
[0067]
Method for preparing thermally conductive gel
[0068] A second aspect of the embodiment of the present application provides a method for preparing the thermally conductive gel provided by the present application, comprising the following steps:
[0069] S1. Mixing raw materials of thermal conductive gel to obtain thermal conductive gel.
[0070] The method for preparing a thermally conductive gel provided in an embodiment of the present application has a very high thermal conductivity and a very thin bonding thickness; wherein the thermal conductivity is 10W / m·k to 15W / m·k, the viscosity is <130Pa·s, the thixotropy is 4 to 7, the viscosity is low G'=50MPa to 80MPa, the shear strength (Si / Ni) is 2MPa to 3MPa, and the BLT is 15μm to 35μm, preferably 20μm to 30μm.
[0071] In some embodiments, in the above step S1, the mixing process includes the following steps:
[0072] S11. After the vinyl silicone oil, hydrogen-containing silicone oil, coupling agent, tackifier, inhibitor and filler are subjected to a first mixing treatment, a second mixing treatment is performed with the catalyst.
[0073] In some embodiments, in the above step S11, the preparation of the filler comprises the following steps:
[0074] S111. After mixing the modified silver powder, modified diamond powder and zinc oxide, stir at a rotation speed of 50 rpm to 100 rpm for 30 min to 40 min.
[0075] In some embodiments, in the above step S111, the preparation of modified silver powder includes the following steps:
[0076] S1111. Dispersing the silver powder into the silver treatment agent and drying to obtain modified silver powder;
[0077] The dosage of the silver treatment agent is 1% to 3% of the mass of the silver powder.
[0078] In some embodiments, in the above step S1111, the silver treatment agent is a mixture of stearic acid organic matter, isopropyl alcohol and water, and the mass ratio of stearic acid organic matter, isopropyl alcohol and water is (40-50):(40-50):1.
[0079] In some specific embodiments, the stearic acid-based organic substance includes at least one of stearic acid and sodium stearate.
[0080] In some specific embodiments, the step of dispersing silver powder into the silver treatment agent comprises:
[0081] The silver treatment agent is sprayed into the silver powder by spraying. In this case, the surface coating and wetting effects are better.
[0082] In some specific embodiments, the silver powder includes 15 to 30 parts by weight of the first silver powder and 65 to 75 parts by weight of the second silver powder; the average particle size of the first silver powder is 250 nm to 350 nm; the average particle size of the second silver powder is 450 nm to 550 nm. In this case, the large and small silver powder particles are compounded to increase the packing density, reduce the gaps, and improve the thermal conductivity of the product.
[0083] In some specific embodiments, the specific surface area of the first silver powder is <1 m 2 / g, the specific surface area of the second silver powder is <0.8m 2 / g. In this case, the specific surface area is small and the viscosity of the final product is low.
[0084] In some specific embodiments, the first silver powder is spherical in shape, and the second silver powder is spherical in shape.
[0085] In some embodiments, in the above step S1111, the drying temperature is 30°C to 50°C, and the drying time is 4h to 6h. It should be noted that the drying device is conventional in the art and does not need to be specifically limited in the embodiments of the present application, but as an example, it can be a blast drying oven.
[0086] In some embodiments, in the above step S111, the preparation of modified diamond powder includes the following steps:
[0087] S1112. dispersing the diamond powder into a diamond treating agent and drying to obtain the modified diamond powder;
[0088] The dosage of diamond treatment agent is 0.5% to 2% of the mass of diamond powder.
[0089] In some embodiments, in the above step S1112, the average particle size of the diamond powder is 0.5 μm to 5 μm.
[0090] In some embodiments, the diamonds are spherical in shape.
[0091] In some embodiments, in the above step S1112, the diamond treating agent is polysiloxane, and the chemical structure is as follows:
[0092]
[0093] Wherein, n>3. In this case, the polysiloxane has a high flash point and is not easily volatile.
[0094] In some specific embodiments, the step of dispersing diamond powder into a diamond treating agent comprises:
[0095] The diamond treatment agent is sprayed into the diamond powder by spraying method. In this case, the surface coating and wetting effects are better.
[0096] In some embodiments, in the above step S1112, the drying temperature is 30°C to 50°C, and the drying time is 4h to 6h. It should be noted that the drying device is conventional in the art and does not need to be specifically limited in the embodiments of the present application, but as an example, it can be a blast drying oven.
[0097] In some embodiments, in the above step S11, the first mixing process includes the following steps:
[0098] S112. After mixing the vinyl silicone oil, hydrogen-containing silicone oil, coupling agent, tackifier and inhibitor, mix them by ultrasonication at 55° C. to 65° C. for 15 min to 25 min to obtain a first mixture.
[0099] S113. After the first mixed liquid and the filler are mixed, they are stirred at a rotation speed of 50 rpm to 100 rpm for 25 min to 35 min, and then stirred at a temperature of 85° C. to 95° C. and a rotation speed of 200 rpm to 250 rpm for 1.5 h to 2.5 h to obtain a second mixed material.
[0100] In some embodiments, in the above step S11, the second mixing process includes the following steps:
[0101] S114. After mixing the second mixed material and the catalyst, stir them for 0.5 h to 1 h under vacuum at a rotation speed of 200 rpm to 250 rpm to obtain the thermal conductive gel.
[0102]
application
[0103] A third aspect of the embodiments of the present application provides an application of the thermally conductive gel provided in the embodiments of the present application in the field of chip heat dissipation.
[0104] The following is further described in conjunction with specific embodiments.
[0105] Example 1
[0106] Embodiment 1 provides a thermally conductive gel, which is composed of the following components in parts by weight:
[0107] 4 parts of vinyl silicone oil, 0.6 parts of hydrogenated silicone oil, 0.2 parts of dodecyltriethoxysilane (coupling agent), 0.2 parts of tackifier, 0.01 parts of acetylene cyclohexanol (inhibitor), 0.03 parts of catalyst, and 92 parts of filler.
[0108] Among them, the vinyl content of vinyl silicone oil is 0.4% and the viscosity is 400cps;
[0109] The hydrogen-containing silicone oil includes 0.3 parts of terminal hydrogen silicone oil and 0.4 parts of side hydrogen silicone oil, wherein the hydrogen content of the terminal hydrogen silicone oil is 0.1% and the viscosity is 20cps, and the hydrogen content of the side hydrogen silicone oil is 0.1% and the viscosity is 70cps;
[0110] The tackifier is UM-DB2152;
[0111] The catalyst is a mixture of chloroplatinic acid and silicone oil, wherein the mass fraction of chloroplatinic acid is 0.5%;
[0112] The filler is composed of the following components in parts by weight: 90 parts of modified silver powder, 15 parts of modified diamond powder and 5 parts of columnar zinc oxide, wherein the average particle size of the columnar zinc oxide is 2 μm.
[0113] This embodiment also provides a method for preparing the thermally conductive gel provided in this embodiment, the steps are as follows:
[0114] S10. Preparation of filler
[0115] S100. Preparation of modified silver powder
[0116] S1000. Select raw materials
[0117] The silver treatment agent is a mixture of stearic acid, isopropyl alcohol and water in a mass ratio of 40:45:1;
[0118] Silver powder: comprising 20 parts by weight of a first silver powder and 70 parts by weight of a second silver powder; the first silver powder has an average particle size of 300 nm and a specific surface area of 0.75 m 2 / g, the average particle size of the second silver powder is 500nm and the specific surface area is 0.5m 2 / g; the first silver powder and the second silver powder are both spherical in shape;
[0119] The dosage of the silver treatment agent is 2% of the mass of the silver powder.
[0120] S1001. Spray the silver treatment agent into the silver powder by spraying, so that the silver powder and the silver treatment agent are evenly dispersed.
[0121] S1002. Dry the uniformly dispersed silver powder and silver treatment agent at 40° C. for 5 hours to obtain modified silver powder.
[0122] S101. Preparation of modified diamond powder
[0123] S1010. Select raw materials
[0124] Diamond powder: average particle size is 3μm, spherical in shape;
[0125] The diamond treatment agent is polysiloxane, and its chemical structure is as follows:
[0126]
[0127] The dosage of diamond treatment agent is 1% of the mass of diamond powder.
[0128] S1011. Spray the diamond treatment agent into the diamond powder by spraying, so that the diamond powder and the diamond treatment agent are evenly dispersed.
[0129] S1012. Dry the evenly dispersed diamond powder and diamond treatment agent at 30°C for 6 hours to obtain modified diamond powder.
[0130] S102. After mixing the modified silver powder, modified diamond powder and zinc oxide, stir at a rotation speed of 50 rpm for 30 minutes to obtain a filler.
[0131] S11. First mixing process
[0132] ① After mixing vinyl silicone oil, hydrogen-containing silicone oil, coupling agent, tackifier and inhibitor, ultrasonically mix at 60° C. for 20 minutes to obtain a first mixture.
[0133] ② After the first mixed liquid and the filler are mixed, they are stirred at a rotation speed of 100 rpm for 30 minutes, and then stirred at a temperature of 90° C. and a rotation speed of 200 rpm for 2 hours to obtain a second mixed material.
[0134] S12. Second Mixing Process
[0135] After the second mixed material and the catalyst were mixed, they were stirred at -0.01 MPa (vacuum) and a rotation speed of 250 rpm for 0.5 h to obtain a thermal conductive gel.
[0136] Example 2
[0137] Embodiment 2 provides a thermally conductive gel, which is composed of the following components in parts by weight:
[0138] 5 parts of vinyl silicone oil, 0.9 parts of hydrogenated silicone oil, 0.1 parts of hexadecyltrimethoxysilane (coupling agent), 0.3 parts of tackifier, 0.02 parts of acetylene cyclohexanol (inhibitor), 0.04 parts of catalyst, and 98 parts of filler.
[0139] Among them, the vinyl silicone oil has a vinyl content of 0.5% and a viscosity of 500cps;
[0140] The hydrogen-containing silicone oil includes 0.4 parts of terminal hydrogen silicone oil and 0.5 parts of side hydrogen silicone oil, wherein the hydrogen content of the terminal hydrogen silicone oil is 0.14% and the viscosity is 25cps, and the hydrogen content of the side hydrogen silicone oil is 0.08% and the viscosity is 80cps;
[0141] The tackifier is UM-T907;
[0142] The catalyst is a mixture of chloroplatinic acid and silicone oil, wherein the mass fraction of chloroplatinic acid is 0.8%;
[0143] The filler is composed of the following components in parts by weight: 105 parts of modified silver powder, 20 parts of modified diamond powder and 7 parts of columnar zinc oxide, wherein the average particle size of the columnar zinc oxide is 4 μm.
[0144] This embodiment also provides a method for preparing the thermally conductive gel provided in this embodiment, and the steps are basically the same as those in Example 1, except that:
[0145] In step S102, the modified silver powder, modified diamond powder and zinc oxide are mixed and stirred at a rotation speed of 75 rpm for 30 minutes to obtain a filler.
[0146] In step S11,
[0147] ① After mixing vinyl silicone oil, hydrogen-containing silicone oil, coupling agent, tackifier and inhibitor, ultrasonically mix at 60° C. for 20 minutes to obtain a first mixture.
[0148] ② After the first mixed liquid and the filler are mixed, they are stirred at a rotation speed of 75 rpm for 35 minutes, and then stirred at a temperature of 85° C. and a rotation speed of 250 rpm for 2 hours to obtain a second mixed material.
[0149] In step S12, the second mixing process
[0150] After the second mixed material and the catalyst were mixed, they were stirred at -0.01 MPa (vacuum) and a rotation speed of 250 rpm for 1 hour to obtain a thermal conductive gel.
[0151] Example 3
[0152] Embodiment 3 provides a thermally conductive gel, which is composed of the following components in parts by weight:
[0153] 3 parts of vinyl silicone oil, 0.5 parts of hydrogenated silicone oil, 0.2 parts of hexadecyltrimethoxysilane (coupling agent), 0.1 parts of tackifier, 0.002 parts of acetylene cyclohexanol (inhibitor), 0.03 parts of catalyst, and 90 parts of filler.
[0154] Among them, the vinyl content of vinyl silicone oil is 0.4% and the viscosity is 400cps;
[0155] The hydrogen-containing silicone oil includes 0.2 parts of terminal hydrogen silicone oil and 0.3 parts of side hydrogen silicone oil, wherein the hydrogen content of the terminal hydrogen silicone oil is 0.11% and the viscosity is 20cps, and the hydrogen content of the side hydrogen silicone oil is 0.12% and the viscosity is 60cps;
[0156] The tackifier is UM-DB2152;
[0157] The catalyst is a mixture of chloroplatinic acid and silicone oil, wherein the mass fraction of chloroplatinic acid is 1%;
[0158] The filler is composed of the following components in parts by weight: 85 parts of modified silver powder, 10 parts of modified diamond powder and 3 parts of columnar zinc oxide, wherein the average particle size of the columnar zinc oxide is 2 μm.
[0159] This embodiment also provides a method for preparing the thermally conductive gel provided in this embodiment, and the steps are basically the same as those in Embodiment 1.
[0160] Comparative Example 1
[0161] Comparative Example 1 proposes a thermally conductive gel, which is composed of the following components in parts by weight:
[0162] 4 parts of vinyl silicone oil, 0.6 parts of terminal hydrogen silicone oil, 0.2 parts of dodecyltriethoxysilane (coupling agent), 0.2 parts of tackifier, 0.01 parts of acetylene cyclohexanol (inhibitor), 0.03 parts of catalyst, and 92 parts of filler.
[0163] Among them, the vinyl content of vinyl silicone oil is 0.4% and the viscosity is 400cps;
[0164] The viscosity of hydrogen-terminated silicone oil is 70cps;
[0165] The tackifier is UM-DB2152;
[0166] The catalyst is a mixture of chloroplatinic acid and silicone oil, wherein the mass fraction of chloroplatinic acid is 0.5%;
[0167] The filler is modified silver powder.
[0168] The preparation steps of the modified silver powder are as follows:
[0169] (1) The silver treatment agent is a mixture of stearic acid, isopropyl alcohol and water in a mass ratio of 40:45:1.
[0170] (2) Selected silver powder: average particle size 300nm, specific surface area 0.75m 2 / g; the amount of silver treatment agent used is 2% of the mass of silver powder.
[0171] (3) The silver treatment agent is sprayed into the silver powder by a spraying method so that the silver powder and the silver treatment agent are evenly dispersed.
[0172] (4) Drying the uniformly dispersed silver powder and silver treatment agent at 40° C. for 5 h to obtain modified silver powder.
[0173] Comparative Example 2
[0174] Comparative Example 2 provides a curable thermally conductive silicone grease stored at room temperature, which includes, by mass: 4.5 parts of vinyl silicone oil with a viscosity of 90mPa·s to 110mPa·s, 1 part of vinyl silicone oil with a viscosity of 270mPa·s to 300mPa·s, 1 part of hydrogenated silicone oil with a hydrogen content of 0.18%, 92.5 parts of pretreated thermally conductive filler and 1 part of an auxiliary agent mixed solution;
[0175] The pretreated thermal conductive filler includes, by weight: 80 parts of spherical aluminum powder, 10 parts of zinc oxide, 10 parts of aluminum oxide, and 0.5 parts of hexadecyltrimethoxysilane;
[0176] The particle size of the spherical aluminum powder, zinc oxide and aluminum oxide is not greater than 20 μm; the auxiliary agent mixed solution comprises, by mass, 93 parts of vinyl silicone oil with a viscosity of 90 mPa·s to 110 mPa·s, 1 part of acetylene cyclohexanol and 6 parts of a pre-treated catalyst;
[0177] The pre-treated catalyst is a catalyst coated with low-temperature wax, and comprises, by mass, 3 parts of chloroplatinic acid isopropanol solution with a platinum content of 0.25% and 3 parts of resin with a softening point of 80°C.
[0178] In order to verify the advancement of the thermally conductive gel and the preparation method thereof provided in the examples of the present application, the thermal interface materials of the examples and the comparative examples were subjected to the following performance tests, and the results are shown in Table 1 below:
[0179] Detection:
[0180] (1) Viscosity: Rheometer, test standard ASTM D2196, test conditions 25±3℃, 60±5%RH, shear rate 5S -1 .
[0181] (2) Thixotropic index (TI): Rheometer was used, the test standard was ASTM D2196, the test conditions were 25±3℃, 60±5%RH, and the shear rate was 0.5S -1 and 5S -1 The ratio of the viscosity below.
[0182] (3) Operating time: using a rheometer, the viscosity was thickened by 20%, and the test conditions were 25±3℃, 60±5%RH, and a shear rate of 5S -1 .
[0183] (4) Thermal conductivity: A HotDisk thermal conductivity meter was used, the test standard was ASTM D5470, and the test conditions were 80°C / 6psi.
[0184] (5) BLT: Using HotDisk thermal conductivity meter, the test standard is ASTM D5470, and the test conditions are 80℃ / 20psi.
[0185] (6) Storage modulus (G'): Rheometer was used, test standard was ASTM D412, and test condition was 150℃ / 2h.
[0186] (7) Shear strength: A thrust test machine was used, the test standard was T / CASAS 018-2021, the chip was SI, the substrate was copper-plated nickel, and the test conditions were: height 280 μm, shear speed 100 μm / s.
[0187] (8) Reliability shear strength retention rate: The ratio of the shear strength of the product after high temperature and high humidity aging at 85℃ / 85%RH / 1000H hours to the initial shear strength.
[0188] The curing conditions of the prepared thermal conductive gel are: 150°C / 2h.
[0189] Table 1
[0190]
[0191] From Table 1 above, we can draw the following conclusions:
[0192] The method for preparing the thermally conductive gel provided in the embodiment of the present application has the following properties: the thermally conductive gel has very high thermal conductivity, very thin bonding thickness and the like; wherein the thermal conductivity is 10W / m·k to 15W / m·k, the viscosity is 90Pa·s to 120Pa·s, the BLT is 20μm to 30μm, and the shear strength is 2MPa to 3MPa.
[0193] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A thermally conductive gel, characterized in that: The raw material components include the following parts by weight: 3 to 5 parts of vinyl silicone oil, 0.4 to 0.9 parts of hydrogen-containing silicone oil, 0.1 to 0.3 parts of coupling agent, 0.1 to 0.3 parts of tackifier, 0.002 to 0.02 parts of inhibitor, 0.02 to 0.04 parts of catalyst, 90 to 98 parts of filler; The filler includes at least one of modified silver powder, modified diamond powder and zinc oxide.
2. The thermally conductive gel according to claim 1, characterized in that: The vinyl silicone oil has a vinyl content of 0.4% to 0.5%; And / or, the viscosity of the vinyl silicone oil is 400cps to 500cps; And / or, the hydrogen-containing silicone oil comprises 0.2 to 0.4 parts of terminal hydrogen silicone oil and 0.3 to 0.5 parts of pendant hydrogen silicone oil.
3. The thermally conductive gel according to claim 2, characterized in that: The hydrogen content of the hydrogen-terminated silicone oil is 0.1% to 0.14% and the viscosity is 20cps to 25cps; And / or, the hydrogen content of the side hydrogen silicone oil is 0.08% to 0.12%, and the viscosity is 60cps to 80cps.
4. The thermally conductive gel according to any one of claims 1 to 3, characterized in that: The filler comprises the following components in parts by weight: 80 to 105 parts of modified silver powder, 10 to 20 parts of modified diamond powder and 3 to 7 parts of zinc oxide; The modified silver powder is obtained by modifying silver powder; The silver powder comprises 15 to 30 parts by weight of a first silver powder and 65 to 75 parts by weight of a second silver powder; The average particle size of the first silver powder is 250nm to 350nm; The average particle size of the second silver powder is 450nm-550nm.
5. A method for preparing the thermally conductive gel according to any one of claims 1 to 4, characterized in that: The steps include: The raw materials of the thermal conductive gel are mixed to obtain the thermal conductive gel.
6. The method for preparing the thermally conductive gel according to claim 5, characterized in that: The mixing process comprises the following steps: After the vinyl silicone oil, hydrogen-containing silicone oil, coupling agent, tackifier, inhibitor and filler are subjected to a first mixing treatment, a second mixing treatment is performed with the catalyst.
7. The method for preparing the thermally conductive gel according to claim 5 or 6, characterized in that: The preparation of the filler comprises the following steps: After the modified silver powder, modified diamond powder and zinc oxide are mixed, they are stirred at a rotation speed of 50 rpm to 100 rpm for 30 min to 40 min.
8. The method for preparing the thermally conductive gel according to claim 6 or 7, characterized in that: The first mixing process comprises the following steps: Vinyl silicone oil, hydrogenated silicone oil, coupling agent, tackifier and inhibitor are mixed, and then ultrasonically mixed at 55° C. to 65° C. for 15 to 25 minutes to obtain a first mixture; After the first mixed liquid and the filler are mixed, they are stirred at a rotation speed of 50 rpm to 100 rpm for 25 min to 35 min, and then stirred at a temperature of 85° C. to 95° C. and a rotation speed of 200 rpm to 250 rpm for 1.5 h to 2.5 h to obtain a second mixed material.
9. The method for preparing the thermally conductive gel according to any one of claims 6 to 8, characterized in that: The second mixing process comprises the following steps: After the second mixed material and the catalyst are mixed, they are stirred for 0.5 h to 1 h under vacuum at a rotation speed of 200 rpm to 250 rpm to obtain the thermal conductive gel.
10. Use of the thermally conductive gel according to any one of claims 1 to 4 in the field of chip heat dissipation.